Sick Populations and Sick Subpopulations: Reducing Disparities in Cardiovascular Disease Between Blacks and Whites in the United States. Issue 6 (9th August 2016) - Lu, Yuan; Ezzati, Majid; Rimm, Eric B.; Hajifathalian, Kaveh; Ueda, Peter; Danaei, Goodarz
Abstract : Background: Cardiovascular disease (CVD) death rates are much higher in blacks than whites in the United States. It is unclear how CVD risk and events are distributed among blacks versus whites and how interventions reduce racial disparities. Methods: We developed risk models for fatal and for fatal and nonfatal CVD using 8 cohorts in the United States. We used 6154 adults who were 50 to 69 years of age in the National Health and Nutrition Examination Survey 1999 to 2012 to estimate the distributions of risk and events in blacks and whites. We estimated the total and disparity impacts of a range of population-wide, targeted, and risk-based interventions on 10-year CVD risks and event rates. Results: Twenty-five percent (95% confidence interval [CI], 22–28) of black men and 12% (95% CI, 10–14) of black women were at ≥6.67% risk of fatal CVD (almost equivalent to 20% risk of fatal or nonfatal CVD) compared with 10% (95% CI, 8–12) of white men and 3% (95% CI, 2–4) of white women. These high-risk individuals accounted for 55% (95% CI, 49–59) of CVD deaths among black men and 42% (95% CI, 35–46) in black women compared with 30% (95% CI, 24–35) in white men and 18% (95% CI, 13–22) in white women. We estimated that an intervention that treated multiple risk factors in high-risk individuals could reduce black-white difference in CVD death rate from 1659 to 1244 per 100 000 in men and from 1320 to 897 in women. Rates of fatal and nonfatal CVD were generally similar between black and white men. In women, a larger proportion of women were at ≥7.5% risk of CVD (30% versus 19% in whites), and an intervention that targeted multiple risk factors among this group was estimated to reduce black-white differences in CVD rates from 1688 to 1197 per 100 000. Conclusions: A substantially larger proportion of blacks have a high risk of fatal CVD and bear a large share of CVD deaths. A risk-based intervention that reduces multiple risk factors could substantially reduce overall CVD rates and racial disparities in CVD death rates. Abstract : Supplemental Digital Content is available in the text.